Relational Database information availability to Semantic Web technologies - Bumans, Guntars (My University, 2014)
Thesis is about possible ways to connect semantic web technologies and relational databases. RDB2OWL language is developed that enable to define mappings between elements of OWL ontology and relational database schema in a concise and human readable form. The language is aimed to get ontology class instances and property values from relational database data, e.g, to generate RDF from relational table data. Promocijas darbā apskatītas Semantiskā tīmekļa tehnoloģiju un relāciju datu bāzu sasaistes iespējas. Izstrādāta valoda RDB2OWL, kas ļauj īsi un cilvēkam lasāmā formā nodibināt atbilstību starp OWL ontoloģijas un relāciju datu bāzes shēmas elementiem ar mērķi iegūt ontoloģijas klašu instances un īpašību vērtības no relāciju datiem, t.i., iegūt RDF trijniekus no tabulu rakstiem.
Keywords: OWL, RDF, RDB; Research Subject Categories::TECHNOLOGY::Information technology